2008
DOI: 10.1194/jlr.m800297-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of apoB secretion from HepG2 cells by insulin is amplified by naringenin, independent of the insulin receptor

Abstract: Hepatic overproduction of apolipoprotein B (apoB)-containing lipoproteins is characteristic of the dyslipidemia associated with insulin resistance. Recently, we demonstrated that the flavonoid naringenin, like insulin, decreased apoB secretion from HepG2 cells by activation of both the phosphoinositide-3-kinase (PI3-K) pathway and the mitogen-activated protein kinase/extracellular-regulated kinase (MAPK erk ) pathway. In the present study, we determined whether naringenin-induced signaling required the insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…32 Previously, it was demonstrated that the citrus flavonoid naringenin potently inhibits apoB100 secretion by activating signaling cascades in HepG2 cells, in a manner similar to insulin. [23][24][25] In contrast to insulin, signaling by naringenin occurs through a mechanism independent of phosphorylation of the insulin receptor. 24,25 Recently, it was reported that naringenin sensitizes hepatocytes to respond to low doses of insulin and potentiates the inhibition of apoB100 secretion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 Previously, it was demonstrated that the citrus flavonoid naringenin potently inhibits apoB100 secretion by activating signaling cascades in HepG2 cells, in a manner similar to insulin. [23][24][25] In contrast to insulin, signaling by naringenin occurs through a mechanism independent of phosphorylation of the insulin receptor. 24,25 Recently, it was reported that naringenin sensitizes hepatocytes to respond to low doses of insulin and potentiates the inhibition of apoB100 secretion.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] In contrast to insulin, signaling by naringenin occurs through a mechanism independent of phosphorylation of the insulin receptor. 24,25 Recently, it was reported that naringenin sensitizes hepatocytes to respond to low doses of insulin and potentiates the inhibition of apoB100 secretion. 24 In a mouse model of insulin resistance (ie, the Western-fed Ldlr Ϫ/Ϫ mouse), the addition of naringenin to the high-fat diet over 4 weeks ameliorated the overproduction of apoB100-containing lipoproteins, attenuated hepatic lipid accumulation, and prevented dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the inhibitory effect of insulin on apoB100 levels appears to involve the phosphatidylinositol 3-kinase signaling cascade, Akt1, a classical downstream effector of phosphatidylinositol 3-kinase, has been shown to have no effect on apoB100 secretion (4). Parallel signaling cascades, such as the mitogen-activated protein (MAP) kinases ERK, p38, and JNK, have been demonstrated to affect apoB secretion (2,3,21,30,37), but knowledge regarding their downstream mechanisms remains limited. Since MAP kinases can be stimulated by both insulin and inflammatory cytokines, and considerable cross talk exists between the insulin signaling cascades and inflammatory pathways, inflammation could play an important role in the overproduction of apoB100-containing lipoproteins observed in insulin-resistant states.…”
mentioning
confidence: 98%